Maternal hygiene and knowledge on complementary feeding during infancy and early childhood in Lahore, Pakistan - Natasha Nadeem; Muhammad Ali; Maryam Javaid Chattha; Momina Ahmed; Mushtaq, Iqra (Journal of the Pakistan Medical Association, 2024)
Objective: To assess practice and knowledge levels regarding complementary feeding among mothers of infants. Method: The analytical cross-sectional study was conducted in CMH Lahore Medical College & Institute of Dentistry, Cantonment, Lahore, Pakistan, from December 2021 to April 2022, and comprised mothers of children aged 6-24 months. Data was collected using a self-administered questionnaire exploring hygiene practices and knowledge related to complementary feeding. Data was analysed using SPSS 23. Results: Of the 117 mothers with mean age 38.5±27.3 years, 115(98.3%) were married and 97(82.9%) resided in urban settings. Among the infants, 70(59.8%) were aged 12-24 months, 55(47%) were first-born, 72(61.5%) were exclusively breastfed for the first 6 months and 45(38.5%) continued breastfeeding along with complementary feeding after 6 months. Hygiene practices correlated to both marital status and the type of family (p<0.05). A significant association was found between mother’s occupation to breastfeeding and hygiene practices (p<0.05). There was no significant association of breastfeeding practices with maternal age and maternal education (p>0.05). Conclusion: Maternal information related to complementary feeding was found to be good, and breastfeeding practices were significantly associated with the mother’s occupation. Maternal hygiene practices were also good, and were significantly associated with the mother’s occupation and type of family. Key Words: Breastfeeding, Child feeding, Child nutrition, Complementary feeding.